2010
DOI: 10.1002/jae.1216
|View full text |Cite
|
Sign up to set email alerts
|

Binary quantile regression: a Bayesian approach based on the asymmetric Laplace distribution

Abstract: SUMMARY This paper develops a Bayesian method for quantile regression for dichotomous response data. The frequentist approach to this type of regression has proven problematic in both optimizing the objective function and making inferences on the parameters. By accepting additional distributional assumptions on the error terms, the Bayesian method proposed sets the problem in a parametric framework in which these problems are avoided. To test the applicability of the method, we ran two Monte Carlo experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 46 publications
1
61
0
1
Order By: Relevance
“…Li et al (2010) showed that the Bayesian quantile regression is robust to 'functional form' terms of use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S1355770X16000255 assumptions; in fact, many Monte Carlo simulations assume that the original error term is normally distributed (Li et al, 2010;Benoit and Van den Poel, 2012) and use the likelihood function of a ALD for the estimation. As Yu and Moyeed (2001) noted, it is not necessary to specify the distribution of the error term.…”
Section: Estimating a Binary Quantile Regressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al (2010) showed that the Bayesian quantile regression is robust to 'functional form' terms of use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S1355770X16000255 assumptions; in fact, many Monte Carlo simulations assume that the original error term is normally distributed (Li et al, 2010;Benoit and Van den Poel, 2012) and use the likelihood function of a ALD for the estimation. As Yu and Moyeed (2001) noted, it is not necessary to specify the distribution of the error term.…”
Section: Estimating a Binary Quantile Regressionmentioning
confidence: 99%
“…is an indicator function, and π(β) is a prior distribution. As in Benoit and Van den Poel (2012), we assume that the prior of the π(β) parameters follows a normal distribution; that is, π(β) ∼ N (β 0 , V 0 ), wherē β 0 is the vector of means of the k × 1 order prior and V 0 is the matrix of variances and covariance of β of k × k order. Although we cannot sample from this unknown posterior distribution, we could use a MCMC algorithm.…”
Section: Estimating a Binary Quantile Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binary QReg models have received considerable interest in the literature and we refer to Manski (1975Manski ( , 1985, Kordas (2006) and Benoit and Poel (2011) for an overview. Suppose y i is a binary outcome variable (e.g.…”
Section: Subset Selection In Binary Qregmentioning
confidence: 99%
“…Therefore, the approach has been useful in many applications (e.g. Yu et al 2005;Yue and Rue 2011;Benoit and Van den Poel 2012;Alhamzawi and Yu 2013;Waldmann et al 2013). …”
Section: Introductionmentioning
confidence: 99%